Pengaruh Penggunaan Media Gambar Berseri Terhadap Kemampuan Menulis Kalimat Sederhana Siswa Sekolah Dasar - Widodo, Arif; Hidayati, Vivi Rachmatul; Fauzi, Asri; Erfan, Muhammad; Indraswati, Dyah (Jurnal DIDIKA: Wahana Ilmiah Pendidikan Dasar, 2020)
The media's role greatly affects the success of the teaching and learning process, which is no exception to writing. One of the stages in writing lessons is to compose a simple sentence. This research aims to determine the influence of the use of image media in the ability to write simple sentences of class IV students at SDN Repok Puyung Tengah Lombok. The main problem in this study is the low ability of students to write simple sentences. This research was designed in the form of experimental research using one group pretest-posttest design approach. Data collection is conducted with test and observation. Research Instrument in the form of writing ability test and observation guideline. Data on research results were analyzed by statistic inferential analysis techniques. The hypothesis was tested with a two-on-average test technique of Paired Sample T-Test. The average pretest value is 65.65 whereas the average value of Postest = 77.05. Based on the hypothesis test results, Sig. = 0.000 Î± = 0.05. Based on the results it can be concluded that the use of the serial image media has enough effect on the ability to write simple sentences of students at SDN Repok Puyung. Key words: image media, writing sentences, elementary school